2008
DOI: 10.1161/circulationaha.108.789008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inherited Thrombophilia on Venous Thromboembolism in Children

Abstract: Background-The aim of the present study was to estimate the impact of inherited thrombophilia (IT) on the risk of venous thromboembolism (VTE) onset and recurrence in children by a meta-analysis of published observational studies. Methods and Results-A systematic search of electronic databases (Medline, EMBASE, OVID, Web of Science, The Cochrane Library) for studies published from 1970 to 2007 was conducted using key words in combination as both MeSH terms and text words. Citations were independently screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(79 citation statements)
references
References 117 publications
1
72
0
6
Order By: Relevance
“…This finding suggests that rs379220 itself is not causal and its association with high Lp(a) and consequently increased CHD risk in Europeans could most likely be explained by the LD with short isoform size that comes with very high Lp(a) levels in Europeans. However, the LD pattern of rs3798220 with other SNPs in LPA appears to be shared between continental groups, thus highlighting the importance of also currently not clear whether the situation is different in children: a meta-analysis of eight studies including almost 600 children with venous thromboembolism and a suitable number of controls found elevated Lp(a) levels to be associated with a more than 4-fold increased risk for the first onset venous thromboembolism, but not recurrent cases (240). Large genetic studies in children are lacking.…”
Section: New Phenotypic Associations Of Lp(a)mentioning
confidence: 99%
“…This finding suggests that rs379220 itself is not causal and its association with high Lp(a) and consequently increased CHD risk in Europeans could most likely be explained by the LD with short isoform size that comes with very high Lp(a) levels in Europeans. However, the LD pattern of rs3798220 with other SNPs in LPA appears to be shared between continental groups, thus highlighting the importance of also currently not clear whether the situation is different in children: a meta-analysis of eight studies including almost 600 children with venous thromboembolism and a suitable number of controls found elevated Lp(a) levels to be associated with a more than 4-fold increased risk for the first onset venous thromboembolism, but not recurrent cases (240). Large genetic studies in children are lacking.…”
Section: New Phenotypic Associations Of Lp(a)mentioning
confidence: 99%
“…In a multicentre study of children with cerebral sinovenous thrombosis (SVT) the presence of the F2 (prothrombin gene) G20210A mutation was found to be associated with an increased risk of recurrence (hazard ratio 4AE3, 95% CI 1AE1-16AE2; P = 0AE034) but F5 R506Q (factor V Leiden; FVL) was not predictive of recurrence (Kenet et al, 2007). A recent systematic review showed that recurrent VTE in children is significantly associated with deficiencies of protein C, protein S and antithrombin, the F2 variant and combined genetic traits (Young et al, 2008).…”
Section: Factors Affecting Recurrence Riskmentioning
confidence: 99%
“…Prominent complicating features of VT in children include lack of thrombus resolution and development of postthrombotic syndrome. [7][8][9] Because of the low incidence of pediatric VT in the general population (0.07-0.14/10 000 population children; ϳ 5/10 000 hospital admissions of children), studies addressing the impact of genetic modifiers of thrombosis on the incidence of pediatric VT are limited by the relatively small number of patients and therefore often remain inconclusive. Meta-analyses of available data suggest that inherited thrombophilic mutations in coagulation factors identified in adult patients (ie, factor V Leiden [FV Leiden ] G1691A, prothrombin G20210A, deficiency of protein S, protein C, and antithrombin) are also the most common genetic determinants of pediatric first VT and ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses of available data suggest that inherited thrombophilic mutations in coagulation factors identified in adult patients (ie, factor V Leiden [FV Leiden ] G1691A, prothrombin G20210A, deficiency of protein S, protein C, and antithrombin) are also the most common genetic determinants of pediatric first VT and ischemic stroke. 7,9,10 The contribution of fibrinogen gene variation to the incidence of VT in children, and the association with the relative abundance of fibrinogen ␥ chain isoforms in plasma is unknown. The goal of the current study was to examine the association between genetic variation in FGG and FGA genes, plasma levels of ␥A/␥Ј fibrinogen, and thromboembolic disease (VT and nonvascular thromboembolic stroke [TS]) in children.…”
Section: Introductionmentioning
confidence: 99%